PETROGENESIS OF VERY LOW-TO LOW-GRADE METAMORPHIC ROCKS IN LUK ULO MÉLANGE COMPLEX, KARANGSAMBUNG, CENTRAL JAVA, INDONESIA - Suhendra, Renaldi (2017)
Very low-to low-grade metamorphic rocks in Karangsambung area are widespread in the Northern Part of Luk UloMélangeComplex especially in Gebang River, Kaliwiro Area, Central Java.This research was conducted in order to understand [1] P and Tcondition of metamorphic rock, [2] protolith variation, [3] relation between these rocks and other rock units, and [4] tectonic environment pre- and syn-metamorphism. The systematic sampling method was conducted to record mineralogical change along Gebang River using petrography, XRD, XRF, and SEM-EDS analyses. Several rocks werecropped outs,whichare scaly clay, mica schist, zeolitic rocks, and basaltic lava, respectively from down- to up-stream. The zeolitic rock consist of celadonite-natrolite-palagonitemeta-basalt, zeolite meta-calcareouspolymictic breccia, zeolite meta-pelite in which based on mineral geochemistry, these rocks are metamorphosed under zeolite-facies (T= 120–220 °C and P= 1–5Kbar). While, mica schist consists of garnet-muscovite-zoisite schist (meta-calcsilicate),garnet-tourmaline-muscovite schist, andgarnet-muscovite greenschist (meta-pelite), as well as garnet-muscoviteortho-greenschist (metabasite) in which from pseudosection analysis, these areincluded intogreenschist-facies(T= 510–580 °C and P= 0.74–1.08 Gpa). Furthermore, very low- to low-grade metamorphic rocks or metamorphosed to un-metamorphosed rocks transitionsaredominantly composed by structural contact. Ortho-rock and meta-peliteprotolith analysis show respectively MORB and island arc affinities before subducted and cropped out in the accretionary wedgeby accretionary type exhumation. New discoveries about Northern part of Luk Ulo Mélange Complex from very low- to low-grade metamorphic rockperspectives, hopefully can be used to complete the geological history in this area. Keyword: zeolite-facies, greenschist-facies, very low- to low-grade metamorphism, Gebang River